Towards Scientific and e-Accounting in Panchayats of Kerala - J.B.Rajan and Biju.S.K (KILA Journal of Local Governance, 2013)
Being the fore-runner of decentralisation, Kerala has introduced a wide range of reforms viz. political, administrative, and fiscal. Fiscal decentralisation is the crux of decentralisation according to ‘finance follows function’ rule. Kerala is the only state in the country having separate budget window for the Local Self Government Institutions (LSGIs); including setting up a fiscal transfer system as the vertical share of local governments. With the fiscal decentralisation, there has been quantum jump in the amount of funds handled by the Panchayats, calling for efficient finance management. In view of this, Govt. of Kerala (GoK) have introduced a scientific accounting system in the Panchayats. Also, initiated e-Accounting by introducing a software entitled ‘Saankya’. This article highlights the initiatives by Kerala on Accrual Based Double Entry System of Accounting (ABDESA) and Saankya implemented in the Panchayats